Knee-Extension Training with a Single-Joint Hybrid Assistive Limb during the Early Postoperative Period after Total Knee Arthroplasty in a Patient with Osteoarthritis - Yoshioka, Tomokazu (Case Rep Orthop, 2016)
The knee range of motion is an important outcome of total knee arthroplasty (TKA). According to previous studies, the knee range of motion temporarily decreases for approximately 1 month after TKA due to postoperative pain and quadriceps dysfunction following surgical invasion into the knee extensor mechanism. We describe our experience with a knee-extension training program based on a single-joint hybrid assistive limb (HAL-SJ, Cyberdyne Inc., Tsukuba, Japan) during the acute recovery phase after TKA. HAL-SJ is a wearable robot suit that facilitates the voluntary control of knee joint motion. A 76-year-old man underwent HAL-SJ-based knee-extension training, which enabled him to perform knee function training during the acute phase after TKA without causing increased pain. Thus, he regained the ability to fully extend his knee postoperatively. HAL-SJ-based knee-extension training can be used as a novel post-TKA rehabilitation modality.